2013
DOI: 10.1590/s0102-09352013000600028
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação nutricional da glicerina vegetal semipurificada para codornas de corte

Abstract: RESUMOForam conduzidos três experimentos com o objetivo de determinar a composição química e os valores de energia metabolizável da glicerina vegetal semipurificada e verificar o desempenho e as características de carcaça de codornas de corte alimentadas com rações contendo níveis crescentes de glicerina. No experimento 1, foram utilizadas 50 codornas, alojadas em gaiolas de metabolismo. Os tratamentos consistiram de uma ração referência e de uma ração teste contendo nível de substituição de 10% de glicerina, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
1
5
0
5
Order By: Relevance
“…Compared with quails fed without the addition of glycerin (control), quails fed with glycerin, considering all levels of inclusion of crude vegetable glycerin to the diet, had increased abdominal fat (Table 3). Similarly to the results obtained in this research, Batista et al (2013) evaluated quails aged 15-35 days fed with levels of inclusion of 4, 8, 12, and 16% of crude vegetable glycerin and semi-purified vegetable glycerin, and observed no significant differences in the yield of carcass, breast, and thigh + drumstick; however, there was a significant difference in the yield of abdominal fat. In contrast, Peña Martínez (2012) evaluated broiler chickens fed a diet containing 2% (age of 1-21 days) and 4% (22-40 days) soy glycerin and found a significant difference in carcass yield but no significant difference in the yield of commercial meat cuts (breast and leg), nor abdominal fat.…”
Section: Resultssupporting
confidence: 68%
“…Compared with quails fed without the addition of glycerin (control), quails fed with glycerin, considering all levels of inclusion of crude vegetable glycerin to the diet, had increased abdominal fat (Table 3). Similarly to the results obtained in this research, Batista et al (2013) evaluated quails aged 15-35 days fed with levels of inclusion of 4, 8, 12, and 16% of crude vegetable glycerin and semi-purified vegetable glycerin, and observed no significant differences in the yield of carcass, breast, and thigh + drumstick; however, there was a significant difference in the yield of abdominal fat. In contrast, Peña Martínez (2012) evaluated broiler chickens fed a diet containing 2% (age of 1-21 days) and 4% (22-40 days) soy glycerin and found a significant difference in carcass yield but no significant difference in the yield of commercial meat cuts (breast and leg), nor abdominal fat.…”
Section: Resultssupporting
confidence: 68%
“…Batista et al (2013) observed values of 95.62% of DM for a semi-purified vegetable glycerin and Rostagno et al (2011) proposed a DM content of 90.00%.…”
Section: Methodsmentioning
confidence: 95%
“…This shows that low inclusion levels of glycerin may not be adequate to determine its energy value, because can be underestimated. Working with the inclusion of 10% vegetable semi-purified glycerin (VSG) in quail diets, Batista et al (2013) obtained a GE value of 3,585 kcal/kg, and an AMEn value of 3,068 kcal/kg (FM), and the MCGE was 85.61%. The authors obtained values of MCDM and MCOM of 88.44 and 90.99%, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em codornas e frangos de corte, a inclusão de glicerol na dieta pode afetar características de desempenho, como ganho de peso e conversão alimentar (Raber et al, 2009;Batista, 2010), além de reduzir ou aumentar a expressão do RNA mensageiro (mRNA) de alguns genes mitocondriais, como a adenina nucleotídeo translocase (ANT) e a proteína desacopladora (UCP), relacionadas à síntese de ATP e ao estresse oxidativo (Gasparino et al, 2012).…”
Section: Introductionunclassified